Using the outdoor scavenger hunt to teach theories of organizational communication. Issue 2 (3rd April 2017) - Tipton, Whitney L.; Kupritz, Virginia W.
Abstract : Courses: Communication Theory, Organizational Communication, Strategic Communication. Objectives: Students will identify and categorize organizational discourses on their campuses; students will become aware of the ethical considerations of communication; students will recognize the different perceptions of organizational culture on campus.